Domestic and International Theoretical Evolution, Research Hotspots and Fronts of Design Innovation and Urban Innovation Ecosystem: -- A CiteSpace-Based Bibliometric Analysis (1999～2024) - Zhang, Qiao; Jiang, Hongbin (Transactions on Social Science, Education and Humanities Research, 2024)
The paper systematically examines domestic and international research trends on the urban innovation ecosystem and their relationship with design innovation from 1999 to 2024 based on CiteSpace bibliometrics analysis. With global economic modernization, technological innovation and institutional innovation have become critical for economic development, with design innovation gaining attention as a bridge connecting the two. By analyzing literature from the Web of Science and CNKI databases, the paper defines relevant concepts and reveals differences in the temporal distribution, hot topics, and research trends between Chinese and international studies. The study finds that international research started early and remains active, while domestic research has rapidly developed under the "mass entrepreneurship and innovation" initiative. Domestic scholars primarily focus on the theoretical exploration and application of ecosystems and innovation ecosystems, whereas international scholars emphasize the application of theoretical frameworks, policy formulation, and social innovation from the perspective of design studies. Design innovation is crucial in promoting collaboration among innovation entities, optimizing resource allocation, driving service innovation, and improving the innovation environment. This paper summarizes the current state of research both domestically and internationally, highlighting the importance of design innovation for future studies and providing valuable references and insights for scholars in related fields.